Fattening Cattle Salt Supplementation and Watering Practices of Urban and Peri-Urban Cattle Fatteners in Dessie and Kombolcha Towns, Ethiopia - Seid, Kassahun Ahmed; Tamir, Berhan; Mengistu, Ashenafi (European Scientific Journal, ESJ, 2017)
The aim of this research was to investigate the cattle fattening system and its structure in urban and peri-urban kebeles of Dessie and Kombolcha towns, Ethiopia where scientific intervention could be initiated for further improvement in fattening practices. In this study structured questionnaire administered to a total of 337 cattle fattener households (190 from Dessie and 147 from Kombolcha towns). Complete enumeration techniques were applied to select urban and peri-urban kebeles. The entire cattle fatteners (100%) in Dessie and Kombolcha towns were provide water for fattening cattle. Pipe and hand wells were the identified water sources in both study towns. 100 % and 49.4 % of peri-urban cattle fatteners in Dessie and Kombolcha towns were totally used hand wells, whereas, the entire urban fatteners (100 %) in both study towns and 50.6 % peri-urban cattle fatteners in Kombolcha town were used pipe as water source for their fattening cattle. The entire cattle fatteners (100 %) in both study towns were provide water for fattening cattle by taking the water to the cattle. Majority of peri-urban (71.8 %, 66.7 %) and the entire urban cattle fatteners (100%, 100%) in Dessie and Kombolcha towns, respectively, were provided water in each day with no watering interval, respectively. 100 % and 75.8% of urban cattle fatteners in Dessie and Kombolcha towns were provided water as a free choice or adl-bitum, whereas, 65.8 % and 90.1 % of peri-urban cattle fatteners were provided dominantly once per day, respectively. In the current both study towns all of urban and peri-urban cattle fatteners (100%) were provide salt for fattening cattle. The entire peri-urban (100 %) and urban (100 %) cattle fatteners in both study towns were provided salt in the form of block or locally called ‘Ganfur’ and via mix with the ration, respectively. Therefore, fattener’s water and salt provision practices should be appreciated and supported with scientific knowledge.